2x - 4 = x + 5
=> 2x - x = 5 + 4
=> x = 9
Vậy x = 9
2x - 4 = x + 5
=> 2x = x + 5 + 4
=> 2x = x + 9
=> 2x - x = 9
=> x = 9
2 x X - 4 = X + 5
2 x X = X + 5 + 4
2 x X = X + 9
2 x X - X = 9
X = 9
2x - 4 = x + 5
2x - x = 5 + 4
Vậy x = 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9
2x - 4 = x + 5
=> 2x - x = 4 + 5
=> x= 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9
2x - 4 = x + 5
2x = x + 5 + 4
2x = x + 9
2x - x = 9
=> x = 9